Second-order interference of two independent and tunable single-mode continuous-wave lasers - 刘建彬 卫栋 陈辉 周宇 郑淮斌 高宏 李福利 徐卓 (Chinese physics B, 2016)
The second-order temporal interference of two independent single-mode continuous-wave lasers is discussed by em- ploying two-photon interference in Feynman＇s path integral theory. It is concluded that whether the second-order temporal interference pattern can or cannot be retrieved via two-photon coincidence counting rate is dependent on the resolution time of the detection system and the frequency difference between these two lasers. Two identical and tunable single-mode continuous-wave diode lasers are employed to verify the predictions. These studies are helpful to understand the physics of two-photon interference with photons of different spectra.